The Role of ESG Factors in Corporate Credit Risk Assessment - Stamenova, Radostina (Research Papers, 2025)
This study examines the role of environmental, social, and governance (ESG) factors in assessing corporate credit risk, with a particular focus on their integration into credit rating methodologies. Through a critical analysis of the scientific literature and the practices of leading credit rating agencies, it is proved that while ESG factors provide an important tool for risk identification, their integration into credit analysis is accompanied by significant challenges. The findings emphasize the need for a phased approach based on transparency, standardized methodology, and data reliability, enabling the validation of rating models while adapting them to the contemporary requirements of sustainable development.
Keywords: Credit rating; Credit risk; Esg factors; Sustainable development